2010
DOI: 10.1007/s00432-010-0957-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of triple-negative breast cancer

Abstract: BackgroundTriple-negative breast cancers (TNBC) neither express hormone receptors, nor overexpress HER2. They are associated with poor prognosis, as defined by low five-year survival and high recurrence rates after adjuvant therapy. Overall, TNBC share striking similarities with basal-like breast cancers (BBC), so a number of studies considered them being the same. The purpose of this review is to summarise the latest findings on TNBC concerning its relation and delineation to BBC, discuss the developmental pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
196
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(208 citation statements)
references
References 82 publications
5
196
0
7
Order By: Relevance
“…This is not surprising because a recent study proved that Bcl-2 is a prognostic factor in women with both ER positive and ER negative disease and also in women with both Her2 negative and Her2 positive disease and its positivity is maintained across various molecular subtypes of breast cancer (Dawson et al, 2010). Although the frequency of Bcl-2 expression ranged from 69-73% in previous studies (Dawson et al, 2010;Kallel-Bayoudh et al, 2011), a controversy exists because they found that TNBC tend commonly to have lower Bcl-2 expression compared to non-TNBC (Tawfik et al, 2010;de Ruijter et al, 2011), moreover, Bcl-2 oncogene expression was found to be statistically greater in the ER positive breast tumors compared to ER negative tumors (dos Santos et al, 2008). Such discrepancies between the studies are likely to be due to the wide variation between the methodologies and types of cases studied (Cecka et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising because a recent study proved that Bcl-2 is a prognostic factor in women with both ER positive and ER negative disease and also in women with both Her2 negative and Her2 positive disease and its positivity is maintained across various molecular subtypes of breast cancer (Dawson et al, 2010). Although the frequency of Bcl-2 expression ranged from 69-73% in previous studies (Dawson et al, 2010;Kallel-Bayoudh et al, 2011), a controversy exists because they found that TNBC tend commonly to have lower Bcl-2 expression compared to non-TNBC (Tawfik et al, 2010;de Ruijter et al, 2011), moreover, Bcl-2 oncogene expression was found to be statistically greater in the ER positive breast tumors compared to ER negative tumors (dos Santos et al, 2008). Such discrepancies between the studies are likely to be due to the wide variation between the methodologies and types of cases studied (Cecka et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Based on histopathological characteristics, the World Health Organization has defined a wide range of invasive breast cancer subtypes (Tavassoli and Devilee, 2003 ). Unfortunately, this way of categorizing breast tumors fails to predict prognosis and treatment possibilities (de Ruijter et al, 2011). Recently, gene-expression analysis-based studies subdivided breast carcinomas into molecular subtypes (Perou et al, 2000;Sorlie et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…While basal-like breast cancer (BLBC) was originally a term used for a molecular subtype, the term TNBC applies to tumors which are negative for expression of ER, PR and HER2 on immunohistochemistry (IHC). Some authors have claimed that the basal type is composed almost entirely of TNBC and therefore, the TNBC phenotype could reliably be used as a surrogate for the basal type (De Ruijter et al, 2011). However, Rouzier et al (2011) revealed that ER and HER2 expression were seen in 5% and 14%, respectively of basal type those had been diagnosed by gene expression profiling.…”
Section: Introductionmentioning
confidence: 99%
“…5 In particular, patients with triple negative breast cancer (TNBC) have the poorest prognosis, with the 5-year survival rate being lower than 30%. 6,7 Therefore, there is an urgent need for developing novel approaches to overcoming the limitations of current breast cancer therapies.…”
Section: Introductionmentioning
confidence: 99%